Micromechanics of dentin/adhesive interface in function of dentin depth: 3d finite element analysis - Anchieta, Rodolfo Bruniera [UNESP]; Rocha, Eduardo Passos [UNESP]; Sundfeld, Renato Herman [UNESP]; Martin Jr., Manoel; Giannini, Marcelo; Reis, André Figueiredo (My University, 2011)
Objectives: The aim of this study was to analyze the stress distribution on dentin/adhesive interface (d/a) through a 3-D finite element analysis (FEA) varying the number and diameter of the dentin tubules orifice according to dentin depth, keeping hybrid layer (HL) thickness and TAǴs length constant. Materials and Methods: 3 models were built through the SolidWorks software: SD - specimen simulating superficial dentin (41 x 41 x 82 μm), with a 3 μm thick HL, a 17 μm length Tag, and 8 tubules with a 0.9 μm diameter restored with composite resin. MD - similar to M1 with 12 tubules with a 1.2 μm diameter, simulating medium dentin. DD - similar to M1 with 16 tubules with a 2.5 μm diameter, simulating deep dentin. Other two models were built in order to keep the diameter constant in 2.5 μm: MS - similar to SD with 8 tubules; and MM - similar to MD with 12 tubules. The boundary condition was applied to the base surface of each specimen. Tensile load (0.03N) was performed on the composite resin top surface. Stress field (maximum principal stress in tension - σMAX) was performed using Ansys Wokbench 10.0. Results: The peak of σMAX (MPa) were similar between SD (110) and MD (106), and higher for DD (134). The stress distribution pathway was similar for all models, starting from peritubular dentin to adhesive layer, intertubular dentin and hybrid layer. The peak of σMAX (MPa) for those structures was, respectively: 134 (DD), 56.9 (SD), 45.5 (DD), and 36.7 (MD). Conclusions: The number of dentin tubules had no influence in the σMAX at the dentin/adhesive interface. Peritubular and intertubular dentin showed higher stress with the bigger dentin tubules orifice condition. The σMAX in the hybrid layer and adhesive layer were going down from superficial dentin to deeper dentin. In a failure scenario, the hybrid layer in contact with peritubular dentin and adhesive layer is the first region for breaking the adhesion. © 2011 Nova Science Publishers, Inc.
Keywords: Adhesive; Dentin; Dentin depth; Dentin tubules; Finite element analysis; Hybrid layer